2022
DOI: 10.1302/0301-620x.104b7.bjj-2021-1775.r1
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the impact of a periacetabular osteotomy on patients’ lives

Abstract: Aims The aim of this study was to understand the experience of mature patients who undergo a periacetabular osteotomy (PAO), a major hip-preserving surgical procedure that treats symptomatic hip dysplasia by realigning the acetabulum. Our aim was to improve our understanding of how the operation affected the lives of patients and their families, with a long-term goal of improving their experience. Methods We used a phenomenological approach with in-depth, semi-structured interviews to investigate the experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…These issues may be further improved using new minimally invasive approaches. 64,65 Our results demonstrated that although there is an increased risk of associated morbidity and perioperative complications, and a longer rehabilitation, 61 PAO can achieve great PROMs and good activity levels even in BHD, in contrast to HA.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These issues may be further improved using new minimally invasive approaches. 64,65 Our results demonstrated that although there is an increased risk of associated morbidity and perioperative complications, and a longer rehabilitation, 61 PAO can achieve great PROMs and good activity levels even in BHD, in contrast to HA.…”
Section: Discussionmentioning
confidence: 61%
“…The aspect of associated morbidity should be carefully considered when choosing to perform PAO. 61 It ranges from psychosocial burden from long rehabilitation to under-recognized debilitating stress fractures. 62 Unlike HA, which has an overall complication rate of 3% in a systematic review including 26,000 cases, PAO has been associated with a 7% complication rate, mostly due to wound problems and higher rates of nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies employed various PROMs to improve the quantification of a patient's experience following PAO; however, there is no consensus on which outcomes should be used. 8,10,[12][13][14][15] Wasko et al 12 analyzed the psychometric properties of hip-specific PROMs and found that the HOOS was most appropriate for patients undergoing PAO. However, HOOS consists of 40 items, hindering its routine use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, validated PROMs for PAO are scarce, and there is no consensus on which outcome should be used. 8,10,[12][13][14][15] Most hip-specific PROMs, including the Hip disability and Osteoarthritis Outcome Score (HOOS), 16 are designed primarily for either OA or THA populations and have shown large ceiling effects when administered to PAO patients. 17 Contrastingly, PROMs developed for younger, active patients with hip disorders, such as the International Hip Outcome Tool (iHOT), have been widely used in hip preservation procedures, 13,18 but not validated in OA, PAO, or THA populations, raising concerns about their generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…We must never forget the great value of our interventions in trauma or orthopaedics. [25][26][27][28][29][30] Trauma and orthopaedic surgeons restore quality of life and that, in turn, improves mobility and almost certainly contributes to longevity. This contribution is often underestimated.…”
Section: Years Youngmentioning
confidence: 99%